KAJIAN HURUF-HURUF MISTERIUS DALAM AL-QURâ€™AN (Al-Ahruf Al-Muqattaâ€™ah) - Rohman, Ali Abdur (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2017)
When we read the Qur'an, then will we find readings that special in it, one of them is there hijaiyah letters contained in the initial letters of the Qur'an. In fact, there is a mention that al-ahruf al-muqatta'ah are mysterious letters. The letters in the discourse of 'ulum Koran known as al-ahruf al-muqatta'ah. These letters are considered foreigners can not understand its meaning in detail and identified. Based on the al-ahruf al-muqatta'ah part of paragraph mutasyabihat. Nonetheless, many scholars have conducted in-depth study on the opening verses of the Koran, so came the differing views and interpretations. In this article the author wants to describe in more detail the views of the commentators for the author presents several sub discussion are: the meaning of al-ahruf al-muqatta'ah, the attitude of scholars towards al-ahruf al-muqatta'ah, wisdom-the wisdom of al-ahruf al-muqatta'ah, the views of the commentators of the meaning of al-ahruf al-muqatta'ah and conclusions. In the end the author concluded that the commentators have different views in dealing with al-ahruf al-muqatta'ah. First, those commentators who choose to interpret al-ahruf al-muqatta'ah. Second, commentators were using takwil al-ahruf al-muqatta'ah. And third, the commentators were being tawaqquf (no interpreting and no using takwil). Keywords: al-Qur’an dan al-ahruf al-muqatta'ah